ANALISIS KELAYAKAN FINANSIAL KELAPA SAWIT RAKYAT DI DESA KARYA BERSAMA KECAMATAN PARENGGEAN KABUPATEN KOTAWARINGIN TIMUR (Studi Kasus Pada Usahatani Sawit Rakyat Ibu Hj. Sunarsih) - Kurniadi, Fery; Pordamantra, Pordamantra; Barbara, Betrixia (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2021)
This research was conducted to know the general description of the smallholder palm oil plantation farming of Mrs. Hj. Sunarsih in Karya Bersama Village and to analyze the financial feasibility of an oil palm plantation run by Mrs. Hj. Sunarsih. The research location was chosen purposively, namely Karya Bersama Village, Parenggean District, Kotawaringin Timur Regency based on the consideration that the most of population in Karya Bersama Village were their living in the agricultural and plantation sectors. Respondent of this research was Mrs. Hj. Sunarsih with consideration of smallholder palm oil plantation of Mrs. Hj. Sunarsih had oil palm trees with the same age were 11 years with this area was 10 hectares and it was the largest in Karya Bersama Village. This research only took the tree age of 11 years palm oil trees planted by Mrs. Hj. Sunarsih in 2009. The data analysis method in this research was qualitative analysis which was processed descriptively based on the result of observation and financial analysis which was processed quantitatively. The result of this research of the financial feasibility analysis of Mrs. Hj. Sunarsih’s oil palm farming during 11 years planting period showed that Mrs. Hj. Sunarsih deserves to be implemented. Based on the financial feasibility investment criteria as follow: a) NPV value at DF 6 % (NPV > 0) namely Rp 458.477.970 ; b) The IRR value is more than the 6 % interest rate on KUR Micro Bank BRI (IRR > i) namely 16,48 % ; c) Gross B/C > 1 namely 1,68 ; d) Net B/C value > 1 namely 2,97 ; and the payback period is relatively fast namely 6,98 (6 years 11 months).